Defoliating of chrysanthemum (Dendrathema morifolium cv. Reagen sunny) for improvement of growth and flower quality. - Tengku Muda Mohamed, Mahmud; S., Abd. Kahar; A., Yahya; S., Shakinah (2001)
A study was conducted to look at the effect of defoliation on growth and flower quality of chrysanthemum (Dendrathema morifolium cv. Reagen Sunny). It was conducted at Protected Crop Production Site, Horticulture Research Centre, MARDI HQ, Serdang, Selangor Darul Ehsan and Postharvest Lab, Department ofCrop Science, Universiti Putra Malaysia (UPM), Serdang, Selangor Darul Ehsan. The treatments arefive levels of defoliation viz. O(control), 20, 40, 60 and 80%. These different levels of defoliation caused significant (p<0. 05) effect on growth and quality characteristics of chrysanthemum. Plant heights, rate of leaf regrowth and stem diameter if not improved, were not affected by defoliation up to 60%. However, fresh and dry weight of leaves, stem, peduncles and flowers decreased with increased levels of defoliation. Vase life was found to improve with 40 and 60% defoliation. Days to showing colour and flower diameter were not affected until 80% of the lower leaves were removed Harvesting date and diameter of inflorescence were respectively increased and reduced with increasing levels of defoliation.